Regional connections of the mediodorsal thalamic nucleus in the rat - (:unkn) unknown (IMR PRESS, 2013)
Thalamic nuclei are classified as first- and higher-order relays. The first-order relays receive their driving afferents from ascending pathways and transmit messages to cortex that cortex has not seen before. The higher-order relays receive driver messages from layer-5 cortical cells for transmission from one cortical area to another. The present study used the retrograde tracer, uoro-gold, to define the afferents to the three regions of the mediodorsal thalamic nucleus, to distinguish which parts contain first- or higher-order relays. The results show that the main inputs to the medial region of the nucleus come from olfactory and visceral structures, those to the central region come from limbic structures and those to the lateral region come from motor centers of the central nervous system. The medial and central regions receive both modulatory (layer 6) and driver (layer 5) afferent inputs from the orbitofrontal and medial frontal areas of the prefrontal cortex whereas the lateral region receives no layer-5 inputs from its cortical connections. Further, the inhibitory modulation of the mediodorsal thalamic nucleus shows regional differences. The medial region receives inhibitory afferents from the striatum (globus pallidus, caudate-putamen), the lateral region from the substantia nigra pars reticulata and the zona incerta, and all segments of the mediodorsal thalamic nucleus receive inhibitory afferents from the thalamic reticular nucleus. The results of the present study show that each region of the mediodorsal thalamic nucleus has distinct afferent connections allowing each region of mediodorsal thalamic nucleus to be considered relatively independent subnuclei that may subserve independent functions.
Keywords: Mediodorsal thalamus; regional; connections; LATERAL GENICULATE-NUCLEUS; PREFRONTAL CORTEX; HIGHER-ORDER; CORTICOCORTICAL COMMUNICATION; GABAERGIC INTERNEURONS; SYNAPTIC ORGANIZATION; AMYGDALOID COMPLEX; LIMBIC SEIZURES; NERVE-CELL; PROJECTIONS